The method for in situ monitoring of the quality of in-vessel mirrors in a fusion reactor - Konovalov, V.G.; Makhov, M.N.; Shapoval, A.N.; Ryzhkov, I.V.; Shtan’, A.F.; Solodovchenko, S.I.; Voitsenya, V.S. (Вопросы атомной науки и техники, 2009)
In laser and optical methods of plasma diagnostics in ITER the most critical components of the measurement schemes will be the First Mirrors (FM) facing the burning plasma and located rather close to plasma volume. It is very important to check regularly the working condition of FM surface in situ, e.g., to control the Quality of transmitted Image (IQ) or signal. In the present work we compare the results of measurements of IQ made in situ, directly on the plasma device DSM-2 during mirror exposure to ion bombardment, with a compact optical scheme in use, and the results of ex situ measurements (on the DIQ stand) – with two times longer distance to mirror (~2.5 meters).